Mycophenolate mofetil in giant cell arteritis - Pankow, Anne; Sinno, Sena; Derlin, Thorsten; Hiss, Marcus; Wagner, Annette D. (Frontiers in Medicine, 2023)
Introduction: Giant cell arteritis (GCA) is a systemic granulomatous vasculitis affecting the large arteries. Abnormal lymphocyte function has been noted as a pathogenic factor in GCA.Mycophenolate mofetil (MMF) inhibits inosine monophosphate dehydrogenase and is therefore a highly lymphocyte-specific immunosuppressive therapy. We aimed to assess the efficacy of MMF for inducing remission in GCA. Methods: 7 patients (5 female, 2 male) with GCA under therapy with MMF and who were treated at the outpatient clinic for rare inflammatory systemic diseases at Hannover Medical School between 2010 and 2023 were retrospectively included in the study. All patients underwent duplex sonography, 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET), magnetic resonance imaging (MRI), and/or biopsy to confirm the diagnosis. The primary endpoints were the number of recurrences, CRP levels at 3-6 and 6-12 months, and the period of remission.Results: All patients in this case series showed inflammatory activity of the arterial vessels in at least one of the imaging modalities: duplex sonography (n=5), 18 F-FDG PET (n=5), MRI (n=6), and/or biopsy (n=5). CRP levels of all patients decreased at the measurement time points 3-6 months, and 6-9 months after initiation of therapy with MMF compared with CRP levels before MMF therapy. All patients with GCA in this case series achieved disease remission.Discussion: The results of the present case series indicate that MMF is an effective therapy in controlling disease activity in GCA, which should be investigated in future randomized controlled trials.